Організація і методика проведення документальних перевірок митними органами - Пилипенко, Ганна Вікторівна; Pylypenko, Hanna Viktorivna (Ірпінь, 2024)
Кваліфікаційна робота полягає у дослідженні організації і методики проведення документальних перевірок митними органами

The qualification work consists in researching the organization and methodology of document checks by customs authorities
Organization and methodology of realization documentary verifications by custom authorities
Keywords: документальні перевірки; інформаційні системи; митні органи; митний контроль; міжнародний товарообіг; documentary verifications; informative systems; customs authorities; custom control; international commodity turnover